Analysis of Presupposition in John Mulaneyâ€™s Stand Up Comedy - Mohammad Muhassin; M. Zaki Dwidandi; M. Ridho Kholid; Dewi Ayu Hidayati (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
This study aims to analyze the types of presupposition used in Stand Up Comedy â€œThere's a Horse in The Hospitalâ€ By John Mulaney on YouTube and to describe the most dominant type of presupposition by using Yuleâ€™s theory. This research used descriptive qualitative method. The data were examined in the form of words, sentences or utterances that contain presuppositions. The findings showed that there were 31 data of presuppositions which consisted of 18 existential presuppositions, 4 factive presuppositions, 4 lexical presuppositions, 2 structural presuppositions, 1 non-factive presupposition, and 2 counterfactual presuppositions. Existential presupposition is the most dominant type which can be seen from the larger amount and percentage of data than others.